Eksklusi Sosial di Bidang Pendidikan Pada Anak-Anak Pengungsi di Indonesia - Taufik Hidayat (Jurnal Sosiologi Andalas, 2022)
Education is significant. Education could give beneficial outcomes for children's future and prevent stress and treat trauma experienced by refugee children. This article examines the process of inequitable education on refugee children in Indonesia by using social exclusion theoretical framework. Different from previous studies that used the law perspective, this study fills the gap in social studies. Literature reviews through Google Scholar and Scopus are used to map inequality education for refugee children in Indonesia. This article reveals that refugee children still hard to enter formal education in Indonesia. However, the Ministry of Education and Culture has already published the regulation that allows refugee children to take formal education. This article also recommends inclusive education for refugee children in Indonesia.